Availability of Infrastructure and Covid-19 Prevention Behavior in Public Place - Lestari, Putri Winda; Dewi, Gusti Kumala (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Public places or facilities are places that can be the locus of the spread of Covid-19. Previous research shows that the application of health protocols in public places is still low in the discipline. The purpose of this study is to find out how the availability of infrastructure impacts the behavior of preventing Covid-19 in public places. This research is a cross-sectional study, with the independent variable being the availability of infrastructure in public places and the dependent variable being the behavior of preventing Covid-19. It took time in 2021. Public places, include malls/shopping centers, traditional markets, places of worship, and public service places. The sample is 264 people with incidental sampling techniques. Data collection was through the distribution of online questionnaires. Data were analyzed by univariate and bivariate with the Chi-Square test (α 0.05). There is a relationship between the availability of infrastructure and behavior in preventing Covid-19 in public places. Public Places with adequate infrastructure are more supportive of the implementation of the behavior of Covid-19 prevention. The government, community leaders, and public place managers must monitor the availability of infrastructure to prevent the spread of Covid-19. There needs to be special attention to the implementation of Covid-19 prevention in public places, especially in traditional markets or street vendors.